KAJIAN TEOLOGIS GEREJA DAN POLITIK: Analisis Transformasi Hubungan dan Keterlibatan Kontemporer - Petonengan, Gerli Safira; Taidi, Alvionita Indasari; Takalamingan, Laura Indah; Metusala, Yuningsi (PT. Giat Konseling Nusantara, 2024)
This study aims to investigate the evolution of the relationship between church and politics from historical to contemporary times, and how the church can effectively engage in modern politics while adhering to Biblical moral and ethical principles. It provides insights into the historical changes in the church-politics relationship and offers practical guidance for the church's ethical participation in today's political arena. The research employs a qualitative descriptive method, utilizing observation and literature review techniques to collect data and analyze how the church can contribute to nation-building and social justice. The findings reveal a significant transformation in the church-politics dynamic, from the dominance of the Catholic Church in the Middle Ages, through the separation of church and state in the modern era, to the church's involvement in current global issues. The church often serves as a moral guide but faces challenges in maintaining integrity and avoiding narrow political interests. The study concludes that the church should act as a moral beacon in politics, emphasizing justice and integrity, and actively participate in advancing social welfare in alignment with Biblical principles.